Thyroid Disease and Surgery in CHEER: The Nation's Otolaryngology–Head and Neck Surgery Practice‐Based Network. (1st July 2016) - Parham, Kourosh; Chapurin, Nikita; Schulz, Kris; Shin, Jennifer J.; Pynnonen, Melissa A.; Witsell, David L.; Langman, Alan; Nguyen‐Huynh, Anh; Ryan, Sheila E.; Vambutas, Andrea; Wolfley, Anne; Roberts, Rhonda; et al.
Abstract : Objectives: (1) Describe thyroid‐related diagnoses and procedures in Creating Healthcare Excellence through Education and Research (CHEER) across academic and community sites. (2) Compare management of malignant thyroid disease across these sites. (3) Provide practice‐based data related to flexible laryngoscopy vocal fold assessment before and after thyroid surgery based on the American Academy of Otolaryngology—Head and Neck Surgery Foundation's clinical practice guidelines. Study Design: Review of retrospective data collection (RDC) database of the CHEER network using ICD‐9 and CPT codes related to thyroid conditions. Setting: Multisite practice‐based network. Subjects and Methods: There were 3807 thyroid patients (1392 malignant, 2415 benign) with 10, 160 unique visits identified from 1 year of patient data in the RDC. Analysis was performed for identified cohort of patients using demographics, site characteristics, and diagnostic and procedural distribution. Results: Mean number of patients with thyroid disease per site was 238 (range, 23‐715). In community practices, 19% of patients with thyroid disease had cancer versus 45% in the academic setting ( P <. 001). While academic sites manage more cancer patients, community sites are also surgically treating thyroid cancer and performed more procedures per cancer patient (4.2 vs 3.5, P <. 001). Vocal fold function was assessed by flexible laryngoscopy in 34.0% of preoperative patients and in 3.7% postoperatively. Conclusion: This is the first overview of malignant and benign thyroid disease through CHEER. It shows how the RDC can be used alone and with national guidelines to inform of clinical practice patterns in academic and community sites. This demonstrates the potential for future thyroid‐related studies utilizing the otolaryngology–head and neck surgery practice‐based research network.